5 - Emerging Questions on the Shifting Sino- Africa Relations: ‘Win-Win’ or ‘Win-Lose’? - Bbaala, Phineas (Africa Development, 2021)
Orthodox scholarly discourse on the theme of Sino-Africa relations has tended to accentuate the efficacy of the South-South alternative to development, chiefly as the vehicle for mitigating the developing countries’ peripheral status in the global order. Literature has accused the North-South economic relations of favouring the former. In search of justice and fair play in international political and economic relations, most African countries started ‘looking east’, mainly towards China. Notwithstanding China’s long solidarity with Africa throughout the liberation struggle, and its contribution to the continent through foreign direct investment, infrastructure development, trade and bilateral aid, some of its recent engagements with the continent have raised questions of neo-colonialism tantamount to those in the North-South relations. The new Sino-Africa relations are being viewed by many as mainly driven by China’s hunger for Africa’s natural resources and the search for international markets for its manufactures, and business opportunities for its multinational corporations. The article argues that the new Sino-Africa economic relations, although still largely ‘win-win’, could soon plunge into ‘win-lose’ relations in favour of China.